Claw lesions and rumen liquor profile in dairy cattle on high grain diet - DEWANGAN, D; SINGH, SWARAN; GREWAL, R S; LAMBA, J S; RANDHAWA, S N S (The Indian Journal of Animal Sciences, 2016)
The present study is conducted to investigate how long the effect of feeding high grains is sustained in the rumen and how this changed or adapted rumen environment is going to affect the hoof health in approximately 10 weeks. Crossbred cows (18) from university dairy farm were divided into 2 groups keeping equal number of animals with same parity in both. Animals in the feeding group were fed with high grain diets for 75 days. The pH, sodium, potassium and different fractions of total volatile fatty acids (TVFA) of rumen liquor were studied every fortnight. All the animals were evaluated for foot lesions before the start of experiment and then at the end of feeding trial. A significant decrease in rumen liquor pH and sodium concentration was observed in the feeding group animals with the progress of time. TVFA concentration increased in the feeding group with rise in acetate, propionate and butyrate levels at the end of the trial. High prevalence of heel erosions, white line haemorrhages, white line fissures and overgrown soles were observed in the feeding group animals at the end of trial along with an increase in rear leg view index. It was concluded that constant feeding of non-structural carbohydrates may increase total volatile fatty acids and frequency of claw lesions in crossbred dairy cattle.